Estimasi Laba Di Masa Yang Akan Datang Dengan Menggunakan Rasio Keuangan Perusahaan - Yanti Budiasih (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2012)
The objectives of the study are to test further empirical findings regarding financial ratio, especially regarding its usefulness in estimating changes in future earnings. This study used 6 samples retail companies that offer shares to the public listed on the Bursa Efek Indonesia by analysis using the 49 financial ratios. Using the method of variable selection stepwise regression were analyzed for the known linear relationship with changes in profit one year, two years and more than two years. The results showed there are significant effects of changes in financial ratios relative to changes in earnings a year to come, there is a significant effect between changes in financial ratios relative to changes in earnings two years from now, and there is a significant effect between changes in financial ratios relative to changes in earnings three years to come.